Arte ampliado
Sobre el Concurso de ampliación Museo Castagnino de Rosario y los proyectos premiados.
Keywords: CONCURSOS; CONCURSOS NACIONALES; PREMIOS; PROYECTOS; PASTO ARQUITECTOS; CARBALLO ERRASTI; CARBALLO, PABLO; ERRASTI, MARICRUZ; ACCOTTO, JUAN PABLO; BARRIO, MAURO IVÁN; BELTRAMONE, ALEJANDRO; COSTA, MARIANO; DE LA MOTA, MARIANO; COCCO, MIGUEL; AMPLIACION; ARGENTINA; SANTA FE [PROV]; ROSARIO; MUSEOS; MUSEOS DE ARTE